Paradisi australi in bilico tra etero e autorappresentazioni: le isole francesi del Pacifico meridionale (Altre Modernità, 2012)
The South Pacific is a region still unimportant in the world scene, where there are islands which are extremely variable in size and are often gathered in archipelagos. Since it was long neglected by the processes of colonialism, the region has managed to preserve a rich environmental and cultural heritage, abundant and unusual in the European hetero-perception. The region was first considered as a far and wild paradise to tame and exploit in the name of geopolitics and the economy, and is now divided into two linguistic areas, English and French. This situation has not prevented the creation of narratives, representations and stereotypes around this idyllic region and its elements of wilderness, mystery, remoteness, exoticism, isolation.This article focuses on the French islands in the South Pacific: New Caledonia, Polynesia and Wallis and Futuna. Beyond their stereotypes and hetero images (tropical paradises, smiling populations), such islands present some extremely varied forms of spatial organization and land management, depending on physical realities, cultural heritage, social, political and economical processes. While traditional tourism promotes the image of tropical paradise, their self-representations are trying to show a different vision, which increases the differences between the three French archipelagos of the South Pacific.